Gestão de conhecimentos e desempenho: evidências de uma amostra de Organizações do Terceiro Setor no Rio de Janeiro - Souza, Joubert Barbosa Assumpção de (2005)
This dissertation examines the implications of the organizational capability for the performance of organizations of the Third Sector. That relationship is examined in a sample of five organizations with headquarters in the city of the Rio de Janeiro, and acting in peculiar segments, like health, childhood and adolescence, sustainable development, environment and social inclusion. The organizational capability was studied from existing analytical frameworks available in the international literature, and adapted for this dissertation. The kinds of empirical evidences are quantitative and qualitative on first hand, and were obtained by multiple techniques: interviews, direct-site observation, exam of documents and casual meetings. These evidences indicators were examined in used in two levels: individual, specific of each one of the organizations, and general, common to all the organizations researched. Concerning organizational capability, the exam of the empirical evidences revealed that the organizations that had had the most significant development in terms of the dimensions identified by Tremblay (1998) as of high performance - that¿s the case of CIEDS and CDI -, were the ones with the best organizational performance. Another relevant point shown by the evidences is the importance of the dimension management attitude to human resources development, similar to previous studies presented by Tremblay (1998), Leonard-Barton (1998) and Figueiredo (2003). The study also shows that the organizations which developed projects aiming at the review and the improvement of managerial practices, approaching them to the models adopted by private companies, had the best performances among the researched group.